1994
DOI: 10.1084/jem.180.4.1225
|View full text |Cite
|
Sign up to set email alerts
|

Bordetella pertussis filamentous hemagglutinin interacts with a leukocyte signal transduction complex and stimulates bacterial adherence to monocyte CR3 (CD11b/CD18).

Abstract: SummaryBordetella pertussis, the causative agent of whooping cough, adheres to human monocytes/macrophages by means of a bacterial surface-associated protein, filamentous hemagglutinin (FHA) and the leukocyte integrin, complement receptor 3 (CR3, ~xmfl2, CDllb/CD18). We show that an FHA Arg-Gly-Asp site induces enhanced R pertussis binding to monocytes, and that this enhancement is blocked by antibodies directed against CR3. Enhancement requires a monocyte signal transduction complex, composed of leukocyte res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
127
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(129 citation statements)
references
References 53 publications
1
127
0
1
Order By: Relevance
“…Furthermore, increased uptake is observed at elevated MOIs and prolonged infection time (data not shown). The fourth possibility is that Brucella infection, especially rough Brucella infection activates the macrophages and up-regulate receptor expression [36]. This assumption is supported by the recent report that the presence of smooth or rough Brucella LPS decreased smooth Brucella uptake, which suggested that, as a legand, LPS compete with Brucella cells for binding sites on macrophages [10,20].…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, increased uptake is observed at elevated MOIs and prolonged infection time (data not shown). The fourth possibility is that Brucella infection, especially rough Brucella infection activates the macrophages and up-regulate receptor expression [36]. This assumption is supported by the recent report that the presence of smooth or rough Brucella LPS decreased smooth Brucella uptake, which suggested that, as a legand, LPS compete with Brucella cells for binding sites on macrophages [10,20].…”
Section: Discussionmentioning
confidence: 82%
“…Our data also suggest that plrS mutants are more susceptible to innate immune mechanisms that function at early stages of infection, perhaps by enhanced clearance by phagocytic cells. Bordetella can interact directly with macrophages (26,28), and previous work using B. bronchiseptica infection of murine lungs has shown that bacterial clearance involves activation of Tolllike receptor 4 and CD11b immune cell signaling pathways (39,50). An important next step in characterization of plrS function will include an evaluation of its contribution to immune cell activity, and toward this end, we have observed that the levels of adherence of plrS mutants to J774 macrophage-like cells in culture are similar to those of wild-type B. bronchiseptica (K. T. Cochran and S. M. Julio, unpublished observations), suggesting that the defect present in plrS strains may exist at a level other than direct interactions with immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the ligation of ␣ v ␤ 3 integrin and integrinassociated protein (IAP) enhances the binding efficiency of CR3 (7,8). This is of particular relevance to C. burnetii infection because macrophages from IAP Ϫ/Ϫ knockout mice exhibit a profound decrease in CR3-mediated phagocytosis of avirulent C. burnetii (5).…”
mentioning
confidence: 99%